Effects of the pattern of glucocorticoid replacement on neural processing, emotional reactivity and well-being in healthy male individuals: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Kalafatakis, Konstantinos; Russell, Georgina; Harmer, Catherine; Munafo, Marcus; Marchant, Nicky; Wilson, Aileen; Brooks, Jonathan; Thai, Ngoc; Ferguson, Stuart; Stevenson, Kirsty; Durant, Claire; Schmidt, Kristin; et al.
Abstract Background Deviation from the physiological glucocorticoid dynamics (circadian and underlying ultradian rhythmicity) is a common characteristic of various neuropsychiatric and endocrine disorders as well as glucocorticoid-based therapeutics. These states may be accompanied by neuropsychiatric symptomatology, suggesting continuous dynamic glucocorticoid equilibrium is essential for brain homeostasis. Methods/design The study consists of two parts. The preliminary stage of the study aims to validate (technically and pharmacologically) and optimise three different patterns of systemic cortisol administration in man. These patterns are based on the combinatory administration of metyrapone, to suppress endogenous cortisol production, and concurrent hydrocortisone replacement. The second, subsequent, core part of the study is a randomised, double-blinded, placebo-controlled, crossover study, where participants (healthy male individuals aged 18–60 years) will undergo all three hydrocortisone replacement schemes. During these infusion regimes, we plan a number of neurobehavioural tests and imaging of the brain to assess neural processing, emotional reactivity and perception, mood and self-perceived well-being. The psychological tests include: ecological momentary assessment, P1vital Oxford Emotional Test Battery and Emotional Potentiated Startle Test, Leeds Sleep Evaluation Questionnaire and the visual working memory task (n-back). The neuroimaging protocol combines magnetic resonance sequences that capture data related to the functional and perfusion status of the brain. Discussion Results of this clinical trial are designed to evaluate the impact (with possible mechanistic insights) of different patterns of daily glucocorticoid dynamics on neural processing and reactivity related to emotional perception and mood. This evidence should contribute to the optimisation of the clinical application of glucocorticoid-based therapeutics. Trial registration UK Clinical Research Network, IRAS Ref: 106181, UKCRN-ID-15236 (23 October 2013)